CONTRASTING MARKED AND UNMARKED QUESTIONS: A CASE OF SIHS IN INDONESIAN - Rika Mutiara (Masyarakat Linguistik Indonesia, 2021)
Discourse marker sih is a common feature of questions in colloquial Indonesian. The results of previous research show a contrast function of sihs in questions. The questions in which sihs occur are called marked questions. The present study explored the functions of sihs by contrasting marked and unmarked questions produced by the same speakers. The marked questions can occur before the unmarked questions or in reverse order. In both patterns, the marked questions indicate speakers’ great willingness to know. They also show speakers’ way to attract hearers’ attention. The unmarked questions were used when the speakers elicit more accurate and precious answers. Moreover, they were uttered when the hearers do not catch the idea mentioned in the first question. They were uttered because the hearers’ ask for repetition.